Емоції в музично-мнемічній діяльності молодших школярів - Рожко, Ірина (Східноєвропейський національний університет імені Лесі Українки, 2017)
У статті з’ясовано місце та роль емоцій у здійсненні музичних мнемічних процесів, досліджено їх вплив на функціонування музичної пам'яті молодшого школяра. Автором конкретизовано зміст понять емоції, емоційний відгук на музику;запропоновано ряд методів, супроводжуючих емоційне запам’ятовування музики, обґрунтовано їх застосування на уроках музичного мистецтва. In this article the place and role of emotions in the implementation of musical mnemonic processes was defined, the influence of emotions on the functioning of the musical memory of the younger schoolchildren was investigated. The author had concretized the content of the concepts of emotion, emotional response to music; had suggested a methods of the emotional memorization of music, had justified their using on lessons of musical art. It was stated that the issue of emotional development of children is widely studied; considerable attention is paid on the lessons of musical art. The practical importance of the research is consisted in generalizing of the advanced pedagogical experience on the problem of interaction of musical memory with emotions and is dictated by the need to update the methods of musical education and upbringing. It was established that the development of emotional responsiveness to music is necessary to carry out from an early age on the basis of the age-related activation of the emotional sphere of children. Because, the ability to perceive and to remember emotions in music develops from early childhood and significantly improves throughout development. It was revealed that the scientific researches of musical psychologists are consistent with the rest literature about the amplifying effect of emotions on the memorization, preservation and reproduction of musical material.
Keywords: емоції; емоційні реакції; музична пам'ять; музично-мнемічна діяльність; емоційний відгук на музику